Rewards of reforms: Can economic freedom and reforms in developing countries reduce the brain drain?. (December 2019) - Aarhus, Jarand H; Jakobsen, Tor G
The objective of this paper is to investigate the impact of economic freedom on brain drain from developing countries to rich countries. Previous literature on brain drain has examined social, political and economic determinants. However, no study in the literature so far has studied this proposed relationship. We employ the Economic Freedom Index sourced from the Fraser Institute as a proxy for economic freedom and the rate of moderately skilled and highly skilled emigration functions as a proxy for brain drain. Our sample consists of 142 countries covering the period 1990–2010. We estimate the results using a two-way fixed effects regression estimator. The results show that an increase in economic freedom is strongly associated with lower levels of brain drain from developing countries to rich countries. In addition, we find that long-term benefits associated with more economic freedom outweigh short-term costs of economic reforms when it comes to restricting brain drain.